The effect of a virtual reality environment on gaze behaviour and motor skill learning - Harris, D. J.; Buckingham, G.; Wilson, M. R.; Brookes, J.; Mushtaq, F.; Mon-Williams, M.; Vine, S. J. (Psychology of Sport and Exercise, 2020)
Highlights: